Predictors of Prediabetic Insidencee among Elderly in Keritang District Indragiri Hilir Riau - Sumandar, Sumandar (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTPrediabetic is a state when glucose level is higher than normal, but does not meet the criteria for diabetes. Elderly people with prediabetic have a higher risk of type 2 diabetes. This observational analytical research was conducted to assess the correlation between sociodemographic and health care behavior of elderly toward incident of prediabetic. The participants were selected according to the inclusion criteria, and 76 participants were selected using cluster sampling and cross sectional approach was used. Multivariate logistic regression was used to estimate the correlation between gender, marital status, education, knowledge, attitude, and practice toward incidence of prediabetic. Data were analyzed using logistic regression test. The results showed that there were no significant differences of gender (p=1.000), marital status (p=1.80), education (p=1.000), and knowledge (p=1.000). Meanwhile, there were significant differences of attitude (p=0.003), practice (p=0.029), and behavior (p=0.012). The Logistic Regression test showed that attitude (OR=5.562) was the predictor of prediabetis incidence among Elderly. The effort to improve and to maintain health status of elderly is by changing the behavior. This can be achieved through an intense cooperation with health promotion team in Primary Health Care, especially nursing community, in a form of education and health promotion with various methods, such as direct intervention, community and elderly empowerment, and sector cross parthership. It is also recommended for Primary Health community to build health centers for elderly to give them access for health service especially for non communicable diseases prevention.ABSTRAKPradiabetes merupakan kondisi kadar glukosa darah di atas normal, tapi belum memenuhi standar diagnosis diabetes. Lanjut usia dengan pradiabetes memiliki peningkatan terhadap Diabetes mellitus tipe 2. Penelitian ini merupakan analitik observasional yang dilakukan untuk mengetahui hubungan antara sosiodemografi dan perilaku perawatan kesehatan lanjut usia terhadap kejadian pradiabetes. Responden yang digunakan telah memenuhi kriteria inklusi dan sampel sebanyak 76 responden yang dipilih secara cluster sampling serta menggunakan metode cross sectional. Data diuji menggunakan regresi logistik. Hasil penelitian ini menunjukkan bahwa tidak ada hubungan antara jenis kelamin (p=1,000), status perkawinan (p=0,80), pendidikan (p=1,00), dan pengetahuan (p=1,000). Sementara itu, terdapat hubungan antara sikap (p=0,003), praktik (p=0,029), dan perilaku (p= 0,012). Hasil uji Regresi Logistik menunjukkan bahwa sikap (OR=5.562) adalah variabel yang paling dominan mempengaruhi insiden pradiabetes. Usaha untuk meningkatkan dan memelihara status kesehatan pada lanjut usia adalah dengan perubahan perilaku. Usaha tersebut melalui kerjasama yang baik dengan tim promosi kesehatan yang ada di Puskesmas, khususnya keperawatan komunitas seperti penggunaan variasi metode pendidikan dan promosi kesehatan, intervensi langsung, pemberdayaan pada masyarakat dan lanjut usia, kerja sama lintas sektor, serta merekomendasikan Puskesmas membangun posyandu lansia agar paralansia bisa memperoleh pelayanan kesehatan terutama pada penyakit tidak menular